The readiness of Quezon City Public Library and its five branches in District IV to support the ALS learners for the Department of Education Accreditation and Equivalency test - Balopiños, Carlos C.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study was conducted to know the information needs of the ALS learners from the 22 ALS Implementers in District IV of Quezon City and to determine the readiness of the Quezon City Public Library and its five branches in District IV. Furthermore, this study aimed to: (1) know which of the subjects or strands of ALS program and learners need additional materials in; (2) know which subject of the ALS program is the most difficult for the ALS learners; (3) know if the ALS learners visit the school library or the public library; (4) know how often they visit the school library and the public library, and; (5) know if ALA learners get sufficient information when they visit the school library and the public library, (6) know whether Quezon City Public Library and its five branches in District IV have information materials which correspond to the subjects in ALS program.
The respondents for this study were 373 ALS learners and six chosen librarians of Quezon City Public Library and its five branches in District IV. There were two types of questionnaires for this study. The first questionnaire, Survey 1, was intended for the ALS learners while the respondents of Survey 2 were the librarians. Three months were spent in doing this research. Survey questionnaires 1 were distributed among the 22 ALS Program Implementers in District IV of Quezon City. The Instructional Managers were the point of contacts in every school. The respondents were the active learners who took the ALS program regularly. Filipino language was used in the survey questionnaires for easy understanding.
The primary information needs of the ALS learners are based on the subject strands of the ALS program, namely: Kasanayang Pangkomunikasyon, Matematika at Agham, English Communication Skills, Kabuhayan at Likas na Yaman, Pagpapalawak Pananaw, and Composition Writing. Their goal is to pass the Accreditation and Equivalency Test given by the Department of Education every year but there is a general observation that ALS Learners lack information materials. Although the library is a big contributor to their information needs, barely half of the population thinks it provides them with sufficient information for ALS program. Math, Science and English are the top three difficult subjects for the ALS learners. A big percentage of the population visit the school library but more than half of the population do not know any public library in their neighborhood. Less than 40 of the population visit the public library and only about 15 think that the public library provides them with sufficient information for ALS. The reason behind this is that Quezon City Public Library and its five branches in District IV have no library programs for the ALS learners. Furthermore, there are not enough public libraries in the entire District IV and not all of them have sufficient information materials for ALS program.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Dropouts -- Philippines -- Quezon City; Equivalency tests -- Philippines -- Quezon City; Public libraries -- Philippines -- Quezon City; Public schools -- Philippines -- Quezon City; Libraries -- Philippines -- Quezon City